Selective histamine uptake rescues photo- and mechanoreceptor function of histidine decarboxylase-deficient Drosophila mutant. - Melzig, J.; Burg, M.; Gruhn, M.; Pak, W.L.; Buchner, E. (Journal of Neuroscience, 1998)
In insects, histamine is found both in the peripheral nervous system (PNS) and in the CNS and is known to function as a fast neurotransmitter in photoreceptors that have been shown to express selectively the hdc gene. This gene codes for histidine decarboxylase (HDC), the enzyme for histamine synthesis. Fast neurotransmission requires the efficient removal of the transmitter from the synaptic cleft. Here we identify in Drosophila photo- and mechanoreceptors a histamine uptake mechanism that can restore the function of these receptors in mutants unable to synthesize histamine. When apparent null mutants for the hdc gene imbibe aqueous histamine solution or are genetically "rescued" by a transgene ubiquitously expressing histidine decarboxylase under heat-shock control, sufficient amounts of histamine selectively accumulate in photo- and mechanoreceptors to generate near-normal electrical responses in second-order visual interneurons and qualitatively to restore wild-type visual and mechanosensory behavior. This strongly supports the proposal that histamine functions as a fast neurotransmitter also in a certain class of mechanoreceptors. A set of CNS-intrinsic neurons that in the wild type contain high concentrations of histamine apparently lacks this uptake mechanism. We therefore speculate that histamine of intrinsic neurons may function as a neuromodulator rather than as a fast transmitter.